2006
DOI: 10.1111/j.1365-2435.2006.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the West, Brown & Enquist model of the allometry of metabolism

Abstract: Summary1. The allometry of metabolic rate has long been one of the key relationships in ecology. While its existence is generally agreed on, the exact value of the scaling exponent, and the key mechanisms that determine its value, are still hotly debated. 3.Here we reconstruct the model and derive the exponent in a clearer and much more straightforward way that requires weaker assumptions than the original model. Specifically, self-similarity of the network is not required. Our formulation can even be used if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 17 publications
(38 reference statements)
0
50
0
1
Order By: Relevance
“…So our branching model, a significant modification of WBE's, predicts the quarterpower scaling exponents including metabolic rate scaling as M Our hierarchical branching model retains the fractal-like design of WBE but shows how the self-similar branching through the hierarchy of arteries arises naturally, with the number of capillaries (proportional to the metabolic rate) scaling as the cube (in 3D animals) of the ratio of the aorta length (∼M 1/3 ) to the capillary length (∼M 1/12 ). Thus, the aorta length scales as the Euclidean length of the organism while ensuring that blood volume scales linearly with M. The changes from WBE-having blood velocity scaling as M 1/12 rather than as M 0 , aorta length scaling as M 1/3 rather than M 1/4 , and average cross-sectional area of the network scaling as M 2/3 rather than M 3/4 -solve the problem of fitting the fractal-like network into an animal with a fundamentally Euclidean geometry (17).…”
Section: The Hierarchical Branching Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…So our branching model, a significant modification of WBE's, predicts the quarterpower scaling exponents including metabolic rate scaling as M Our hierarchical branching model retains the fractal-like design of WBE but shows how the self-similar branching through the hierarchy of arteries arises naturally, with the number of capillaries (proportional to the metabolic rate) scaling as the cube (in 3D animals) of the ratio of the aorta length (∼M 1/3 ) to the capillary length (∼M 1/12 ). Thus, the aorta length scales as the Euclidean length of the organism while ensuring that blood volume scales linearly with M. The changes from WBE-having blood velocity scaling as M 1/12 rather than as M 0 , aorta length scaling as M 1/3 rather than M 1/4 , and average cross-sectional area of the network scaling as M 2/3 rather than M 3/4 -solve the problem of fitting the fractal-like network into an animal with a fundamentally Euclidean geometry (17).…”
Section: The Hierarchical Branching Networkmentioning
confidence: 99%
“…It initiated a lively debate about the empirical generality of 3/4-power metabolic scaling and its theoretical explanation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). A recent study revived the case for geometric scaling by showing that simple models of distribution networks generate metabolic scaling exponents of 2/3 (25).…”
mentioning
confidence: 99%
“…There have been only a few attempts to give a mechanistic explanation for the statistical variability although both the scaling exponent and the normalization constant may have an interpretation based on biological processes (Kozłowski et al 2003;Etienne et al 2006;Mäkelä and Valentine 2006;Chown et al 2007;Enquist et al 2007;Price et al 2007). As an alternative, some process-based models use conditional values of a and b, or additional variables to modify the values of a and b, instead of attempting to give a direct interpretation of the values of a and b by themselves (Duursma et al 2007;Holdo 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, several rigorous empirical analyses, involving body sizes spanning several orders of magnitude, have shown that b often deviates substantially from 3/4, varying significantly among different taxonomic groups of animals and plants (Glazier 2005;Reich et al 2006;White et al 2006White et al , 2007, and among different physiological states (Glazier 2005;Niven & Scharlemann 2005;White & Seymour 2005;Makarieva et al 2005aMakarieva et al , 2006b). Second, the models supporting the so-called 3/4-power law appear to have flawed assumptions and serious mathematical inconsistencies that have not yet been resolved, despite much debate (Dodds et al 2001;Kozlowski & Konarzewski 2004, 2005Brown et al 2005;Makarieva et al 2005bMakarieva et al , 2006aPainter 2005b,c;Banavar et al 2006;Chaui-Berlinck 2006, 2007Etienne et al 2006;Savage et al 2007).…”
Section: Introductionmentioning
confidence: 99%